Late‐News Paper: A Real 3D Image Projected "Out‐of‐the‐Box" using Dual Parabolic Reflectors. Issue 1 (June 2014) - Li, Kenneth
Abstract This paper presents a newly developed high brightness Tru3D "Out of the Box" 3D Display without using a screen or special glasses, which produces true 3‐dimensional "floating" images of real objects and LCD display images. This system, using Dual Parabolic Reflectors (DPRTM), creates the appearance of a 3‐D product hovering in mid‐air, outside of the confines of a display case, to draw customer attention as such locations at trade shows, malls and other retail outlets. A 3" version, for small objects like diamond rings, has been built and demonstrated. A 17" version for larger objects is being built for demonstration. In addition, the Tru3D display can be used for ATM's and other secure transition kiosk using active keyboards such that the user can inputs the PIN numbers in mid‐air without others seeing the entered codes.